2018
DOI: 10.1186/s13063-017-2397-2
|View full text |Cite
|
Sign up to set email alerts
|

Clinical research ethics review process in Lebanon: efficiency and functions of research ethics committees – results from a descriptive questionnaire-based study

Abstract: BackgroundClinical trials conducted in Lebanon are increasing. However, little is known about the performance of research ethics committees (RECs) in charge of reviewing the research protocols. This study aimed to assess the level of adherence to the ethics surrounding the conduct of clinical trials and perceptions of team members regarding roles of the RECs during the conduct of clinical trials in Lebanon. The research question was: Are RECs adherent to the ethics surrounding the conduct of clinical trials (c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…In the current study, more than a third of the researchers did not have training in research ethics. Inadequate research ethics training was demonstrated in several studies conducted in developing countries . A survey of the faculty members at Cairo University in Egypt showed that almost half of them never attended a course in research ethics .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the current study, more than a third of the researchers did not have training in research ethics. Inadequate research ethics training was demonstrated in several studies conducted in developing countries . A survey of the faculty members at Cairo University in Egypt showed that almost half of them never attended a course in research ethics .…”
Section: Discussionmentioning
confidence: 99%
“…Inadequate research ethics training was demonstrated in several studies conducted in developing countries. [24][25][26] A survey of the faculty members at Cairo University in Egypt showed that almost half of them never attended a course in research ethics. [27] Giving the gaps in research ethics in the Middle East countries, [26] it is clear that research ethics training is necessary to improve ethical standards in the conduct of academic and biomedical research.…”
Section: Discussionmentioning
confidence: 99%
“…Using emails (as in the case of the Delphi), participants may feel that their input is restricted to their respective fields of specialties. Using the Delphi technique requires a high motivation level on behalf of the participants to respond to their emails (Health Knowledge, 2016). In Lebanon, participation and response rate using emails are less common, and response rate could constitute a barrier (Atallah et al, 2018; Bizri et al, 2020), a context that may raise concern of lack of contribution of participants. The latter cited as a main reason for using the NGT (Manera et al, 2019).…”
Section: Methodsmentioning
confidence: 99%
“…Clinical research activity involving human subjects is increasing in developing countries (Atallah et al, 2018; Normile, 2008). In today's research environment, Institutional Review Boards (IRBs) are fundamental to the protection of human research participants (Rwabihama et al, 2010).…”
Section: Introductionmentioning
confidence: 99%